The CIPP Model-Based Evaluation on Information Technology Competence Certification Program at Universitas Brawijaya - Muhammad Imron Hamdani; Imam Hanafi (Sekolah Pascasarjana Universitas Brawijaya, 2021)
In higher education, the development of Information Technology (IT) requires all academics to be able to adapt to the change of information. In Universitas Brawijaya, certification is carried out as a means to increase student competence in entering the workforce, this is stated in Rector Regulation number 36 of 2015. The CIPP evaluation model is a comprehensive evaluation format that has stages of context, input, process, and product. This study aims to determine and assess the implementation of competency certification programs as well as supporting and inhibiting factors measured by the CIPP evaluation method. This study using a qualitative approach with descriptive methods. Data collection techniques with observation, documentation, literature study, and in-depth interviews. The results showed that in the context aspect there was a relevance between the Ministry of Higher Education and Universitas Brawijaya. The input aspect of the components in this aspect is good but the students need more stimulus to be more proactive towards the program. The process is good to be seen from the responses of the participants but needs more supervision in the aspects of the exam of the product are good from the results of the value achieved also a benefit that is felt by the participants.